Proceedings of the 4th Workshop on Argument Mining 2017
DOI: 10.18653/v1/w17-5110
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised corpus–wide claim detection

Abstract: Automatic claim detection is a fundamental argument mining task that aims to automatically mine claims regarding a topic of consideration. Previous works on mining argumentative content have assumed that a set of relevant documents is given in advance. Here, we present a first corpuswide claim detection framework, that can be directly applied to massive corpora. Using simple and intuitive empirical observations, we derive a claim sentence query by which we are able to directly retrieve sentences in which the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 12 publications
0
48
0
Order By: Relevance
“…For the topic-dependent claim detection task, Levy et al (2017) showed that retrieving sentences with the word that followed by the concept representing the topic, yields candidates that are more likely to contain a claim for that topic than arbitrary sentences which contain the topic concept.…”
Section: Sld and Wld In Argumentation Miningmentioning
confidence: 99%
“…For the topic-dependent claim detection task, Levy et al (2017) showed that retrieving sentences with the word that followed by the concept representing the topic, yields candidates that are more likely to contain a claim for that topic than arbitrary sentences which contain the topic concept.…”
Section: Sld and Wld In Argumentation Miningmentioning
confidence: 99%
“…Given a controversial topic, several queries are applied, retrieving sentences which potentially contain claims that are relevant to the topic. Query results are then ranked by a neural-model trained to detect sentences containing claims (similarly to Levy et al (2017Levy et al ( , 2018 ). Top-ranked sentences are passed to a boundary detection component, responsible for finding the exact span of each claim within each sentence (Levy et al, 2014).…”
Section: Mining Claimsmentioning
confidence: 99%
“…The claim lexicon is a lexicon containing words with argumentative characteristics. Levy et al (2017) use the appearance of the term "that" as a weak signal of sentences containing argumentative components. After collecting nearly 1.86M sentences, they compute the prior probability of the term "that" P (that) occurring in a sentence, and the probabilities P (that|w i ), where P (that|w i ) denotes the probability of a sentence having the term "that" and the word w i is in the suffix after the main concept (i.e.…”
Section: Lexicon Resourcementioning
confidence: 99%